IMPLEMENTATION MODERN FORMS OF LIFELONG LEARNING IN UKRAINE - But, Vladimir; Panchenko, Ganna (Continuing Professional Education: Theory and Practice, 2019)
In this article delineated modern forms of lifelong learning, such as: formal, non-formal and informal. It is indicated that in contrast to formal education the non-formal and informal education hasn’t time limits, are not systematic, hasn’t age, professional or even intellectual limitations on their participants in the educational process. The organization of lifelong learning can be implemented in various forms, which differ in the degree of involvement of computer tools, target orientation, covering different age audiences, time of holding classes and so on. It is allocated priority tasks of modern Ukrainian education, in particular such aspects that relating to the implementation of education in Ukraine the principles of lifelong learning. It is analyzes trends of their implementation in the education system of Ukraine from education «early learning» to education of «third age». It is indicated that the EU, in contrast to education system of Ukraine, emphasizes the importance for non-formal and informal education, their relevance certify regulations of UNESCO, EU, UN, ILO, etc. Considered legal and regulatory framework of Ukraine on regulation and support the implementation of new forms of lifelong learning in Ukrainian higher education. In particular, the Draft Law of Ukraine «On Education» defines the notion of «formal education», «non-formal education» and «informal education» as modern forms organization of lifelong learning. It is outlined the necessity of promotion of development in Ukraine non-formal and informal forms of education beside with a formal one in order to ensure the principles of lifelong learning. There is a necessity in developing criteria and improving mechanisms for recognition and strengthening non-formal and informal forms of education in educational and professional activities.